Efficacy and safety of glecaprevir/pibrentasvir in patients with chronic HCV infection and psychiatric disorders: An integrated analysis. Issue 8 (20th May 2019) - Back, David; Belperio, Pamela; Bondin, Mark; Negro, Francesco; Talal, Andrew H.; Park, Caroline; Zhang, ZhenZhen; Pinsky, Brett; Crown, Eric; Mensa, Federico J.; Marra, Fiona
Abstract: Although direct‐acting antivirals (DAAs) for chronic hepatitis C virus (HCV) infection are highly efficacious and safe, treatment initiation is often limited in patients with neuropsychiatric disorders due to concerns over reduced treatment adherence and drug–drug interactions. Here, we report adherence, efficacy, safety and patient‐reported outcomes (PROs) from an integrated analysis of registrational studies using the pangenotypic DAA regimen of glecaprevir and pibrentasvir (G/P). Patients with chronic HCV genotypes 1‐6 infection with compensated liver disease (with or without cirrhosis) receiving G/P for 8, 12 or 16 weeks were included in this analysis. Patients were classified as having a psychiatric disorder based on medical history and/or co‐medications. Primary analyses assessed treatment adherence, efficacy (sustained virologic response at post‐treatment week 12; SVR12), safety and PROs. Among 2522 patients receiving G/P, 789 (31%) had a psychiatric disorder with the most common diagnoses being depression (64%; 506/789) and anxiety disorders (27%; 216/789). Treatment adherence was comparably high (>95%) in patients with and without psychiatric disorders. SVR12 rates were 97.3% (768/789; 95% CI = 96.2‐98.5) and 97.5% (1689/1733; 95% CI = 96.7‐98.2) in patients with and without psychiatric disorders, respectively. Among patients with psychiatric disorders, SVR12 rates remained >96% by individual psychiatric diagnoses and co‐medication classes. Overall, most adverse events (AEs) were mild‐to‐moderate in severity with serious AEs and AEs leading to G/P discontinuation occurring at similarly low rates in both patient populations. In conclusion, G/P treatment was highly efficacious, well‐tolerated and demonstrated high adherence rates in patients with chronic HCV infection and psychiatric disorders.